Novel Benzothiazole-based Ureas as 17β-HSD10 Inhibitors, A Potential Alzheimer's Disease Treatment - Aitken, Laura; Benek, Ondrej; McKelvie, Brogan E; Hughes, Rebecca E; Hroch, Lukas; Schmidt, Monika; Major, Louise L; Vinklarova, Lucie; Kuca, Kamil; Smith, Terry K; Musilek, Kamil; Gunn-Moore, Frank J (Molecules (Basel, Switzerland), 2019)
: It has long been established that mitochondrial dysfunction in Alzheimer's disease (AD) patients can trigger pathological changes in cell metabolism by altering metabolic enzymes such as the mitochondrial 17β-hydroxysteroid dehydrogenase type 10 (17β-HSD10), also known as amyloid-binding alcohol dehydrogenase (ABAD). We and others have shown that frentizole and riluzole derivatives can inhibit 17β-HSD10 and that this inhibition is beneficial and holds therapeutic merit for the treatment of AD. Here we evaluate several novel series based on benzothiazolylurea scaffold evaluating key structural and activity relationships required for the inhibition of 17β-HSD10. Results show that the most promising of these compounds have markedly increased potency on our previously published inhibitors, with the most promising exhibiting advantageous features like low cytotoxicity and target engagement in living cells.
Keywords: Alzheimerova nemoc; buněčné linie; molekulární struktura; 17β-hydroxysteroid dehydrogenase type 10 (17β-HSD10), amyloid binding alcohol dehydrogenase (ABAD), benzothiazole; lidé; Humans; benzothiazoly; Alzheimer’s disease (AD), amyloid-beta peptide (Aβ), mitochondria; racionální návrh léčiv; Drug Design; močovina; Molecular Structure; Amyloid beta-Peptides; Dose-Response Relationship, Drug; 17-hydroxysteroidní dehydrogenasy; amyloidní beta-protein; 17-Hydroxysteroid Dehydrogenases; mitochondrie; Benzothiazoles; Mitochondria; vztah mezi dávkou a účinkem léčiva; Alzheimer Disease; vztahy mezi strukturou a aktivitou; Cell Line; Urea; Structure-Activity Relationship